Letter from Arnold O. Beckman to Dr. T. J. Glover - Beckman, Arnold O. (1935)
Beckman discusses cancer treatment options for his friend and colleague, Dr. Amos A. Noyes, and offers to provide Glover with a pH meter.
Keywords: Hydrogen-ion concentration--Measurement--Instruments; Scientific apparatus and instruments; Noyes, Arthur A. (Arthur Amos), 1866-1936; Hydrogen-ion concentration; Beckman Instruments, Inc.